1996
DOI: 10.1111/j.1439-0418.1996.tb01629.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and behavioural responses of chestnut moths, Cydia fagiglandana and C. splendana (Lep., Tortricidae), to sex attractants and odours of host plants

Abstract: EAG recordings were made from both males and females of Cydia fagiglandana (Zell.) and C. splendana (Hb.) on stimulation with the tortricid sex attractants (E,E)‐8,10‐dodecadien‐l‐yl acetate (E8E10‐12:Ac), (E,E)‐8,10‐dodecadien‐l‐ol (E8E10‐12:OH) and (Z)‐8‐dodecen‐l‐yl acetate (Z8‐12:Ac). The dose‐response curves of the various attractants were almost identical for males of both species. The order of increasing EAG sensitivity was E8E10‐12:OH < Z8‐12:Ac < E8E10‐12:Ac. In females, EAGs increased in the order E8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 18 publications
0
42
0
2
Order By: Relevance
“…Den Otter et al, 1996;Hansson et al, 1989;Schneider et al, 1998), including C. pomonella (Ansebo et al, 2004), and the central processing of sex pheromone information in females has previously been studied in S. littoralis (Anton and Hansson, 1995;Ochieng et al, 1995;Sadek et al, 2002) and H. virescens (Hillier et al, 2006). In codling moth females, pheromone components elicited a response in PNs innervating a group of OGs in the lateral region of the AL, close to the entrance of the AN; these PNs also responded to a number of plant volatiles (Table2, Fig.3D, Fig.4B).…”
Section: Integration Of Behaviourally Relevant Chemical Cuesmentioning
confidence: 99%
“…Den Otter et al, 1996;Hansson et al, 1989;Schneider et al, 1998), including C. pomonella (Ansebo et al, 2004), and the central processing of sex pheromone information in females has previously been studied in S. littoralis (Anton and Hansson, 1995;Ochieng et al, 1995;Sadek et al, 2002) and H. virescens (Hillier et al, 2006). In codling moth females, pheromone components elicited a response in PNs innervating a group of OGs in the lateral region of the AL, close to the entrance of the AN; these PNs also responded to a number of plant volatiles (Table2, Fig.3D, Fig.4B).…”
Section: Integration Of Behaviourally Relevant Chemical Cuesmentioning
confidence: 99%
“…These actometers have been shown to be sensitive enough to record flight and locomotor activity of individual insects such as tsetse flies (Van der Goes van Naters, Den Otter, & Maes, 1998), moths (Den Otter, De Cristofaro, Voskamp, & Rotundo, 1996;Renou, Berthier, Desbarats, Van der Pers, & Guerrero, 1999), Anopheles mosquitos ( Van de Broek, Den Otter, & Van der Pers, 1999), and fruit flies (Knoppien, Van der Pers, & Van Delden, 2000). In the present study, we describe a homemade microwave radar device for monitoring locomotor activity in insects and small mammals.…”
mentioning
confidence: 99%
“…Specifically, exposure to pheromone advances and/or increases the level of female calling in some species, which is thought to increase the probability of attracting a mate (Palanaswamy & Seabrook, 1985;Stelinski et al, 2006). It has also been suggested that autodetection may provide a mechanism by which females maximally distribute themselves among limited host-plant resources (den Otter et al, 1996). Others have speculated that female capability for detecting their pheromone may result in aggregations of females increasing local probability of attracting males (Birch, 1977) or that it may serve as a mechanism for lek formation (Schneider et al, 1998).…”
Section: Discussionmentioning
confidence: 99%